El masacre se pasa a pie e a reconstrução do massacre de haitianos na fronteira domínico-haitiana: história e ficção - Suriel, Richard Junior (2014)
This dissertation presents a reflection on history and fiction from the reconstruction of the slaughter of haitians, in 1937, on the northern border of the Dominican Republic and Haiti, two countries that then formed the island of Hispaniola , when the arrival of Christopher Columbus in the New World. The body of this fictional work in the novel The Slaughter passed on foot, the writer and lawyer dominican Freddy Prestol Castillo, published in 1978 in the Dominican Republic. Our hypothesis to develop this work was that to rebuild the haitian genocide in fiction , the author claims the dictatorship of Rafael Leónidas Trujillo (1930-1961) , the Trujillato , focusing on racism , prejudice , violence and aspects negative nourished in the collective memory of the dominican elite to support a historic rejection of haitians. We use a theoretical framework that allows us to look for links between history and fiction in the aforementioned novel and that it was necessary to seek the historical facts recorded the various invasions of Hispaniola, from the concept of racism Memmi (1967) and memory, Halbwachs (1990).